2015
DOI: 10.1364/oe.23.002879
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and high speed modulation characteristics for AlGaInAs/InP microdisk lasers

Abstract: Thermal and high speed modulation characteristics are investigated for a unidirectional-emission microdisk laser with a radius of 7 μm surrounded by BCB-cladding layer, with a threshold current of 1.5 mA at the temperature of 287 K. The lasing spectra under different widths of pulsed current are measured to characterize the temperature rise during the pulse period, and the thermal distribution in the microdisk laser is simulated by the finite-element modeling technique. A temperature rise of 25 K is estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…More recently SSM response with 3-dB bandwidth up to 20 GHz was demonstrated for the AlGaInAs/InP microdisk laser with active region based on 6 QWs with a radius of 7 µm surrounded by BCB-cladding layer [85]. Eye diagrams at the bit rates of 20, 25, and 30 Gbit/s were also measured at the temperature of 14 • C [85].…”
Section: Dynamic Characteristics and Data Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently SSM response with 3-dB bandwidth up to 20 GHz was demonstrated for the AlGaInAs/InP microdisk laser with active region based on 6 QWs with a radius of 7 µm surrounded by BCB-cladding layer [85]. Eye diagrams at the bit rates of 20, 25, and 30 Gbit/s were also measured at the temperature of 14 • C [85].…”
Section: Dynamic Characteristics and Data Transmissionmentioning
confidence: 99%
“…The disadvantage of InP-based microlasers is caused by small energy offsets and low thermal conductivity [87], which results in a significant deterioration of their characteristics with temperature increase. For instance, in reference [85], it was observed that when the temperature rises from 14 to 40 • C, the resonance frequency value drops from 14.9 to about 8.3 GHz. However, dynamic characteristics of much more temperature stable GaAs-based MD lasers are poorly studied.…”
Section: Dynamic Characteristics and Data Transmissionmentioning
confidence: 99%
“…1(a), which can be fabricated under a less precise process compared with the microdisk lasers evanescently coupled with a waveguide. 17 Furthermore, the mode wavelengths and the full-width at half maximum (FWHM), obtained by fitting the resonant peak with a Lorentzian function, are plotted in Figs. The microdisk resonator was laterally confined by a benzocyclobutene (BCB) cladding layer with a refractive index of 1.54.…”
Section: Static Characteristicsmentioning
confidence: 99%
“…Микродисковые лазеры [1,2] активно исследуются в последние годы в связи с перспективами их использования в качестве компактных источников для систем оптической связи на кристалле. Оптический резонатор таких лазеров формируется с помощью глубокого травления эпитаксиальной гетероструктуры сквозь волновод и активную область.…”
unclassified